Endoscopic dilation of dominant stenoses in primary sclerosing cholangitis: outcome after long-term treatment - Gotthardt, Daniel; Rudolph, Gerda; Klöters-Plachky, Petra; Kulaksiz, Hasan; Stiehl, Adolf (Gastrointestinal endoscopy, 2010)
Background - Primary sclerosing cholangitis is characterized by progressive fibrotic inflammation and obliteration of intra- and/or extrahepatic bile ducts. Total or subtotal stenoses of major bile ducts are associated with reduced survival. - Objective - To evaluate the outcome after long-term endoscopic treatment. - Design - Prospective, single-center study. - Setting - Tertiary care academic medical center. - Patients - A total of 171 patients treated with ursodeoxycholic acid were followed for as long as 20 years. At entry, 20 patients had dominant stenoses, and during a median follow-up period of 7.1 years, dominant stenosis developed in another 77. - Interventions - Ninety-six patients with dominant stenoses were treated by repeated balloon dilation; 5 patients with complete obstruction with bacterial cholangitis were stented. - Main Outcome Measurements - Survival free of liver transplantation, number of procedures, complications. - Results - In total, 500 balloon dilations were performed and 5 stents were placed. Complications were pancreatitis (2.2%), bacterial cholangitis (1.4%), and bile duct perforation (0.2%); there were no deaths. Repeated endoscopic interventions allowed the preservation of a functioning common bile duct and of at least 1 hepatic duct up to 2 cm above the bifurcation in all patients. Progression of intrahepatic bile duct and liver disease led to the need for liver transplantation in 22 of 96 patients. Five years after the first dilation of a dominant stenosis, the survival free of liver transplantation rate was 81%, and after 10 years, it was 52%. - Limitations - Single-center study, no control group, primary end-stage liver disease excluded. - Conclusion - Repeated endoscopic balloon dilations of dominant stenoses allow the preservation of a functioning common bile duct for many years.
Gesehen am 27.04.2023